Pengaruh Pemakaian Kontrasepsi Suntik DMPA Terhadap Peningkatan Berat Badan Pada Akseptor KB di Puskesmas Tompobulu-Gowa - Jumrana Jumrana; Asmaul Husnah (Lembaga Pengembangan Kinerja Dosen, 2023)
Contraception as a form of prevention of pregnancy is one of the essences of family planning problems (KB) officially used by the National Family Planning Coordinating Board (BKKBN). One type of effective contraception that mothers choose is the type of injectable contraception. To determine the effect of DMPA injection use on weight gain in family planning acceptor in Puskesmas Tompobulu Gowa. Analytical observational with cross sectional study approach. This research was conducted at Puskesmas Tompobulu Kab. Gowa on 31 July - 31 August 2017. The sample in this study is total sampling with as many as 51 respondents of the instrument in this study is using a questionnaire. Statistical test using computerized system by using chi-square test at significance level 95% (α = 0,05). The Result of this research is p-value = 0.000 with significance level <0,05. This shows that there is significant influence between the duration of contraceptive use to weight gain. And obtained by p-value = 0,002 with significance level <0,05 this shows there is significant influence of physical activity activity to weight gain. The longer duration of use of DMPA injection will be more at risk of obesity on contraceptive injectors. The fewer activities performed by the KB acceptor will be more at risk of weight gain. This research is expected to be useful and become input for practice area in giving injection contraception service and observe acceptor body weight every time at visit.